Whole-Genome Sequencing Revealed a Late-Maturing Isogenic Rice Koshihikari Integrated with Hd16 Gene Derived from an Ise Shrine Mutant - Motonori Tomita; Ryotaro Tokuyama; Shosuke Matsumoto; Kazuo Ishii (International Journal of Genomics)
We identified the key genes controlling the late maturation of the Japonica cultivar Isehikari, which was found at Ise Jingu Shrine and matures 6 days later than Koshihikari. We conducted a genetics-based approach through this study. First, the latest mature plants, which flowered later than Isehikari, were segregated in the F2 and F3 generations of Koshihikari×Isehikari. Next, the linkage relationship of a single late-maturing gene with the SSR markers on the long arm of chromosome 3 was inferred by using late-maturing homozygous F2 segregants. Moreover, genetic analyses of late maturity were conducted through the process of six times of continuous backcross with Koshihikari as a recurrent parent by using the late-maturing homozygous F3 line as a nonrecurrent parent, thus developing a late-maturing isogenic Koshihikari (BC6F2). As a result, we elucidated a single late-maturing gene with incomplete dominance that caused the 14-day maturation delay of Koshihikari. The whole-genome sequencing was conducted on both of Koshihikari and the late-maturing isogenic Koshihikari. Then, the SNP call was conducted as the reference genome of Koshihikari. Finally, a single SNP was identified in the key gene Hd16 of the late-maturing isogenic Koshihikari.